2009
DOI: 10.1007/s11085-009-9158-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Levels of Strontium on the Oxidation Behavior of Selected Molten Aluminum–Magnesium Alloys

Abstract: The effects of small additions of strontium on the oxidation behavior of aluminum-magnesium alloy melts were investigated by thermogravimetry at 750°C for times up to 48 h. Oxidized samples were examined by FEGSEM, and phases formed within the oxide layer and in the alloy were identified by EDS, WDS and low-angle X-ray diffraction techniques. In the absence of Sr, the Al-Mg samples gained substantial amounts of weight by formation of spinel (MgAl 2 O 4 ) at the oxide-metal interface. Samples containing Sr had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Previous studies on the effects of Sr on the oxidation have shown mixed results with its effectiveness for inhibiting oxidation. [13,14] Rare earth elements stand out as a potential alternative as they are surface active and will readily react. Yttrium has seen usage as an alloying element to reduce the oxidation of solid Mg alloys at 500°C and may prove effective in controlling the oxidation of liquid AlMg alloys.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effects of Sr on the oxidation have shown mixed results with its effectiveness for inhibiting oxidation. [13,14] Rare earth elements stand out as a potential alternative as they are surface active and will readily react. Yttrium has seen usage as an alloying element to reduce the oxidation of solid Mg alloys at 500°C and may prove effective in controlling the oxidation of liquid AlMg alloys.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that alloying with strontium (Sr) decreased the oxidation rate of Al alloys [176,177]. Aydin and co-workers [178] studied the oxidation behaviour of Mg-2.5 wt.% Sr and Mg-6 wt.% Sr alloys in the solid state at 500 C.…”
Section: Srmentioning
confidence: 99%
“…In 2004, Pekguleryuz and Vermette [14] compared the amount of oxide formed on commercial AZ91D containing 9 ppm Be with the AZ91E (<0.001 wt% Be þ 75 ppm Sr) alloy. The weight gain measurements showed that similar amounts of oxides formed on each alloy and that Be could be replaced by Ozdemir et al [15] showed that the surface activity of Sr in Al-Mg alloys decreases the oxidation rate by suppressing spinel crystal formation and forming a Sr-enriched region that acts as a barrier to inward oxygen diffusion. Aydin et al [16] found that the T i of pure Mg increased from 640 to 860°C with the addition of 6 wt% Sr.…”
Section: Introductionmentioning
confidence: 97%